Influence of Teachers’ Attitude on Pupils Reading Readiness in Low-Cost Private Multi-Grade Pre-Primary Schools in Nairobi City County, Kenya - Oketch, A. Violet; Mugo, W. Juliet; Mweru, Maureen (African Journal of Education and Practice, 2025)
Purpose: Reading is the foundation of all learning, essential for comprehending information across all subjects. Preparing pupils for reading depends significantly on teacher attitude, among other factors. Despite this understanding, poor reading performance is a global concern. This study assessed the influence of teachers’ attitudes on pupils’ reading readiness, specifically in low-cost private multi-grade preschools. The focus was on this foundational level of reading and future learning, examining how teachers manage mixed-ability and mixed-age groups. Methodology: Guided by bandura’s (1977) social learning theory, this study employed a correlational design. Simple random sampling was used to select a 15% sample (50 schools, teachers, and head teachers) from 350 low-cost private multi-grade pre-primary schools. Data were collected via questionnaires and interview schedules. Instrument validity was ensured by aligning content with research objectives, and reliability was established using the split-half technique (coefficient of 0.7). Data were analyzed both qualitatively and quantitatively. Pearson’s correlation coefficient was used to test the hypotheses. Findings: The study found a statistically significant relationship between teacher attitude and pupils’ reading readiness (r = 0.042, p < 0.05). Unique Contribution to Theory, Practice and Policy: The study recommends that school management implement regular training programs for teachers in multi-grade pre-primary schools and improve teacher remuneration.